O papel do colegiado escolar no processo de democratização da gestão : um estudo de caso no Colégio Estadual José Malta Maia - Pessoa, Carlos Magno (2009)
Over the years the educational system has been changing from technicaladministrative actions in search of a concrete foundation of social and political development. The democratization and participatory management has been a benchmark in the process of organization and reorganization of the educational system favoring the establishment of school councils in order to allow greater interaction and encourage the participation and involvement of all those who are part of the school daily life. By the laws governing the educational system and with reference to some theoretical research this question, this study sought to examine the role of the School Council in José Malta Maia State College, located in Jiquiriçá / BA, seeking to investigate the characteristics of management in the mentioned unit as well its decision-making process, application of financial resources and the participation of segments of the school community in this reality.